1999
DOI: 10.1051/aas:1999293
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray burst positions from the ASM on RXTE

Abstract: Abstract. The RXTE/ASM has detected and positioned 14 confirmed GRB bursts (at this writing, Jan. 1999) including six whose positions were communicated to the community 2 to 32 hours after the burst. Two of these latter bursts led to measurements of optical red shifts but one, despite an easily detected X-ray afterglow, produced no detectable optical or radio afterglow.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…4U 0142+61 monitoring data of the PCA (2-60 keV; Jahoda et al 1996) on board the Rossi X-ray Timing Explorer (RXTE, Bradt et al 1993) were used to create a phase-coherent timing solution valid during the multiwavelength campaign (see Gavriil and Kaspi 2002, for a detailed description and use of the AXP-monitoring campaign). This ephemeris is essential for INTEGRAL timing analysis (cf., den Hartog et al 2007).…”
Section: Rossi-xtementioning
confidence: 99%
“…4U 0142+61 monitoring data of the PCA (2-60 keV; Jahoda et al 1996) on board the Rossi X-ray Timing Explorer (RXTE, Bradt et al 1993) were used to create a phase-coherent timing solution valid during the multiwavelength campaign (see Gavriil and Kaspi 2002, for a detailed description and use of the AXP-monitoring campaign). This ephemeris is essential for INTEGRAL timing analysis (cf., den Hartog et al 2007).…”
Section: Rossi-xtementioning
confidence: 99%
“…PACS numbers: 97.60.Jd, 97.80.Jp, 04.80.Cc Until now about twenty LMXBs have been discoveried to exhibit kHz QPOs, include one X-ray pulsar, with the Rossi X-ray Timing Explorer (RXTE) since the early 1996, briefly after its launch [1][2][3]. The Z sources (Atoll sources), which are high (less) luminous neutron-star lowmass X-ray binaries [4], typically show four distinct types of QPOs [1].…”
mentioning
confidence: 99%
“…The relations ν H vs. ν 2 and ∆ν vs. ν 1 are plotted in Fig.1 and Fig.2, together with the well measured source samples, and it is shown that the agreement bewteen the model and the observed QPO data is quite well for the selected values of the NS mass from 1.4 to 1.8 M ⊙ , which is the solely free parameter in the Eqs. (1)(2)(3)(4)(5). From Eqs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The implications for our techniques are explained where appropriate below (and see Appendix). Calibration is undertaken by the ASM/RXTE team and the processed data are freely accessible on their website 2 (Bradt et al 2001). The RXTE counts are not directly proportional to luminosity, so the exact relationship between these two quantities would have to be accounted for in any model.…”
Section: Introductionmentioning
confidence: 99%